(untitled) (Bangladesh Journal of Plant Taxonomy, 2005)
Eight species of the genus Leucas R. Br. (Lamiaceae) have been recognized for Bangladesh after critical studies and described them in the paper with artificial key, illustrations and other necessary information. Keywords: Leucas R. Br., Lamiaceae, Taxonomy, Bangladesh. DOI: 10.3329/bjpt.v12i1.607 Bangladesh J. Plant Taxon. 12(1): 1-10, 2005 (June)